KEARIFAN LOKAL DI KABUPATEN KEPULAUAN MERANTI - Nurahim Rasudin (Jurnal Ilmu Hukum, 2022)
This study aims to identify local wisdom in the Meranti Islands Regency. The method used in this research is a juridical-normative research which focuses on library data research. The normative juridical approach, namely the method used by adhering to the juridical aspects, by carrying out an inventory of positive laws relating to the problems studied. Juridically, local governments have the authority to increase the capacity of local wisdom or traditional knowledge and the rights of local wisdom or traditional knowledge related to the environment in the regencies/cities. Local wisdom in Meranti Islands Regency, there are approximately 300 types of local wisdom. Of these, they can be grouped into 5 (five) major groups. Namely, local wisdom related to agriculture, local wisdom in the culinary field, local wisdom in the natural resource management sector (peat), local wisdom in the field of traditional games and sports, and local wisdom in the field of fisheries and marine affairs.